Primary extraoral sclerosing microcystic adenocarcinoma of the salivary gland - Elizabath Priya Mathew; Christina A. MacMillan; David P. Goldstein; Stephen M. Smith (Elsevier, 2021)
Sclerosing microcystic adenocarcinoma (SMA) of the salivary gland is an extremely rare entity described in the mucosal sites of the head and neck region. These tumours are noteworthy for their histological resemblance to cutaneous microcystic adnexal carcinoma (MAC). Here, we describe about an unusual parotid tumour which showed remarkable similarity to cutaneous MAC. In this report we will be discussing about the diagnostic dilemma created by this tumour as this entity was not previously described in the parotid gland, the differential diagnosis considered along with a brief review of literature.